Involvement of cyclin-dependent kinase-like 2 in cognitive function required for contextual and spatial learning in mice - Gomi, Hiroshi; Sassa, Takayuki; Thomson, Richard F.; Itohara, Shigeyoshi (Frontiers in Behavioral Neuroscience, 2010)
Cyclin-dependent kinase-like 2 (Cdkl2) is a cdc2-related serine/threonine protein kinase that is postnatally expressed in various brain regions, including the cerebral cortex, entorhinal cortex, hippocampus, amygdala, and dorsal thalamus. The extremely high Cdkl2 expression in these regions suggests that it has a role in cognition and emotion. Recent genetic studies indicate that mutations of Cdkl family kinases are associated with neurodevelopmental and neuropsychiatric disorders in humans. To elucidate the physiologic role of Cdkl2, we behaviorally analyzed Cdkl2LacZ/LacZ mice lacking Cdkl2. Cdkl2LacZ/LacZ mice had reduced latencies to enter the dark compartment after electric footshock in an inhibitory avoidance task and attenuated contextual fear responses when exposed to mild training conditions. Hippocampal spatial learning in the Morris water maze was slightly anomalous with mice exhibiting an abnormal swimming pattern. The aversive response in a two-way avoidance task was slightly, but not significantly, enhanced. On the other hand, Cdkl2LacZ/LacZ mice did not exhibit altered sensitivity to aversive stimuli, such as electric footshock and heat, or deficits in the elevated plus maze or rotating rod test. These findings suggest that Cdkl2 is involved in cognitive function and provide in vivo evidence for the function of Cdkl family kinases expressed in terminally differentiated neurons in mice.